Axisymmetric stress distribution around an isolated fiber fragment - Whitney, James M.; Drzal, Lawrence T.
An analytical model is presented for predicting the stresses in a system consisting of a broken fiber surrounded by an unbounded matrix. The model is based on classical theory of elasticity and is applicable to the stress analysis of a single-fiber interfacial shear strength test specimen. Stresses in the vicinity of the broken fiber are approximated by a decaying exponential function multiplied by a polynomial. An exact solution is obtained for the far field stresses away from the broken end of the fiber. The fiber is assumed to be transversely isotropic. The model also includes the effect of expansional strains as a result of moisture and temperature. Numerical results are presented for AS-4 graphite fiber and Kevlar 49 aramid fiber embedded in an epoxy matrix. Predicted values of critical fiber lengths are compared to experimentally measured values.
Keywords: GRAPHITE - FIBERS; MATERIALS TESTING; MATHEMATICAL MODELS; STRESSES - ANALYSIS